Studien zur unteritalischen Vasenmalerei - Schauenburg, Konrad, 1921-2011. (Kiel Kiel Kiel Kiel Kiel Kiel Kiel)
10 cilt 7 ciltte (2. c. 167 s. ; 3. c. 152 s. ; 4-5. c. 224 s. ; 6. c. 144 s. ; 7-8. c. 190, [1] s. ; 9-10. c. 222 s. ; 11-12. c. 208 s.)